2013
DOI: 10.3390/molecules181012663
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Molecular Aspects of Tetrahydrocannabinol and Cannabidiol as Antioxidants

Abstract: An antioxidant mechanism of tetrahydrocannabinol (THC) and cannabidiol (CBD) were compared with a simplified model of α-tocopherol, butylhydroxytoluene and hydroxytoluene in order to understand the antioxidant nature of THC and CBD molecules using DFT. The following electronic properties were evaluated: frontier orbitals nature, ionization potential, O-H bond dissociation energy (BDE OH ), stabilization energy, and spin density distribution. An important factor that shows an influence in the antioxidant proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 42 publications
3
75
0
Order By: Relevance
“…THC has ameliorative effects as anti‐inflammatory and antioxidant . THC serves as cannabinoid receptors (CBs) agonist and plays a regulatory role in the expression of CBs and function of the pancreatic β cell .…”
Section: Discussionmentioning
confidence: 99%
“…THC has ameliorative effects as anti‐inflammatory and antioxidant . THC serves as cannabinoid receptors (CBs) agonist and plays a regulatory role in the expression of CBs and function of the pancreatic β cell .…”
Section: Discussionmentioning
confidence: 99%
“…Due to the hydroxyl groups (C-1 and C-5 in the B ring), CBD can also bind to amino acids such as threonine, tyrosine, glutamic acid, or glutamine by means of a hydrogen bond [17]. CBD has potential antioxidant properties because its free cationic radicals exhibit several resonance structures in which unpaired electrons are distributed mainly on ether and alkyl moieties, as well as on the benzene ring [18].…”
Section: Introductionmentioning
confidence: 99%
“…The authors noted that there was a greater efficacy against glutamate‐induced neurotoxicity than with ascorbate or α‐tocopherol. This suggests that CBD has potential therapeutic application in neurodegenerative disorders associated with OS …”
Section: Resultsmentioning
confidence: 98%
“…This suggests that CBD has potential therapeutic application in neurodegenerative disorders associated with OS. 13,17,18,33,[37][38][39][40][41] Rajan et al evaluated the anti-inflammatory, antioxidative and anti-apoptotic effects of low doses of CBD. The results showed that 5 lM CBD had a moderate anti-inflammatory effect (TNF-a, IL-10) and oxidative markers (inducible nitric oxide synthase, nuclear factor erythroid 2-related factor 2, nitrotyrosine).…”
Section: Phasementioning
confidence: 99%